REPRESENTASI KETERASINGAN TERHADAP LINGKUNGAN DALAM LAGU LAST ROAR (2019) KARYA TUAN TIGABELAS - Jena Sinanda (Haluan Sastra Budaya, 2023)
In Indonesia, the existence of tigers in the Sumatra Forest is threatened because of industrialization, which destroys the balance of nature and impacts the tiger habitat. Tuan Tigabelas is one of the Indonesian singers who used the song, "Last Roar" (2019), as a medium to vocalize the deforestation issue in Sumatra from the tiger's perspective. This study aims to reveal the alienation of the environment in Last Roar, which can be used to raise ecological awareness through the discourse of forest exploitation in Sumatra. Gerard Genette's narratological theory and Simon Hailwood's concept of alienation are used to analyze nature's representation through the tiger's point of view and the impact of the exploitation of nature presented in Last Roar. The hip-hop music genre combined with traditional Sumatra music shows that there are serious issues related to the environment that many people should pay attention to.